Geminin regulates cortical progenitor proliferation and differentiation - Spella, Magda; Kyrousi, Christina; Kritikou, Eva; Stathopoulou, Athanasia; Guillemot, François; Kioussis, Dimitris; Pachnis, Vassilis; Lygerou, Zoi; Taraviras, Stavros (Stem cells, 2011)
During cortical development, coordination of proliferation and differentiation ensures the timely generation of different neural progenitor lineages that will give rise to mature neurons and glia. Geminin is an inhibitor of DNA replication and it has been proposed to regulate cell proliferation and fate determination during neurogenesis via interactions with transcription factors and chromatin remodeling complexes. To investigate the in vivo role of Geminin in the maintenance and differentiation of cortical neural progenitors, we have generated mice that lack Geminin expression in the developing cortex. Our results show that loss of Geminin leads to the expansion of neural progenitor cells located at the ventricular and subventricular zones of the developing cortex. Early cortical progenitors lacking Geminin exhibit a longer S-phase and a reduced ability to generate early born neurons, consistent with a preference on self-renewing divisions. Overexpression of Geminin in progenitor cells of the cortex reduces the number of neural progenitor cells, promotes cell cycle exit and subsequent neuronal differentiation. Our study suggests that Geminin has an important role during cortical development in regulating progenitor number and ultimately neuron generation.